Preparation and characterisation of resin-based dental composites using natural hydroxyapatite and silica fillers - Rafiq Akram Che Razali (Tanjong Malim, 2021)
Preparation and characterisation of resin-based dental composites using natural hydroxyapatite and silica fillers by Rafiq Akram Che Razali